PKM DAWIS SAKURA DALAM MELAKSANAKAN PROGRAM JOGO TONGGO DI RW 9 KELURAHAN GONDORIYO KECAMATAN NGALIYAN KOTA SEMARANG PROPINSI JAWA TENGAH - rinayati rinayati; Harsono Harsono; Cempaka Kumala Sari; Safira Fegi Nisrina (Jurnal Implementasi Pengabdian Masyarakat Kesehatan (JIPMK), 2021)
The implementation of this PKM activity focuses on providing assistance to Dasawisma cadres in carrying out the Jogo Tonggo Program from the Central Java Provincial Government in the RT 05 RW 9 environment in particular and Gondoriyo Village in general. Dasa Wisma cadres are at the forefront who play a role and contribute to efforts to mobilize citizens to face the Covid 19 pandemic, through the active role of Dawis Sakura cadres in RT 5 RW 9, Gondoriyo Village, Ngaliyan District, Semarang City in socializing to embrace and invite the community, of course, they are expected to be able to fight Covid Transmission 19 in the neighborhood of RT 5 RW 9, Gondoriyo Village, Ngaliyan District, Semarang. Based on the conditions and problems felt by these partners, the servant makes efforts that begin with. a) Pre Field Survey, b) Socialization and c) Assistance in implementing the Jogo Tonggo Program. The solution offered to partners is the socialization of the Jogo Tonggo Program in the form of socialization and mentoring of Dawis Sakura cadres in implementing the Jogo Tonggo Program. The Jogo tonggo program at Dawis Sakura has been formed and has an organizational structure in the form of a chairman and members, the jogo tonggo activity at Dawis Sakura is a monthly activity of 1000, garbage alms, environmental cleanliness work, distribution of masks, handsanitizers, groceries, spraying disinfectant liquid in RT 5 environment and a mosquito nest eradication program. Publication of this article in a national service journal. and a youtube link.